2023
DOI: 10.1021/acs.jmedchem.2c00775
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Virtual Screening Identifies a 2-Aryl-4-aminoquinazoline Series with Efficacy in an In Vivo Model of Trypanosoma cruzi Infection

Abstract: Probing multiple proprietary pharmaceutical libraries in parallel via virtual screening allowed rapid expansion of the structure–activity relationship (SAR) around hit compounds with moderate efficacy against Trypanosoma cruzi, the causative agent of Chagas Disease. A potency-improving scaffold hop, followed by elaboration of the SAR via design guided by the output of the phenotypic virtual screening efforts, identified two promising hit compounds 54 and 85, which were profiled further in pharmacokinetic studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The bioluminescent T. cruzi CL Brener (TcVI) strain has been widely used for in vivo imaging in murine models of Chagas disease, particularly in the context of drug testing [eg. 9,16,25,[27][28][29]. This parasite line (T. cruzi CLBR-Luc) was generated by transfection with vector pTRIX2-RE9h (S1 Fig) [13,30], which targeted the PpyRE9h red-shifted luciferase gene [31] to a high expressing ribosomal DNA (rDNA) locus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The bioluminescent T. cruzi CL Brener (TcVI) strain has been widely used for in vivo imaging in murine models of Chagas disease, particularly in the context of drug testing [eg. 9,16,25,[27][28][29]. This parasite line (T. cruzi CLBR-Luc) was generated by transfection with vector pTRIX2-RE9h (S1 Fig) [13,30], which targeted the PpyRE9h red-shifted luciferase gene [31] to a high expressing ribosomal DNA (rDNA) locus.…”
Section: Resultsmentioning
confidence: 99%
“…Causes skeletal muscle fibrosis and spastic diplegia in hamsters [50]. Widely used as a model for drug testing in combination with BALB/c mice [25,[27][28][29]51]. 10 Causes gastrointestinal transit time delay in C3H/HeN mice [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, new strategies to increase the efficiency of finding drug prototypes must be implanted in the routine workflow . In this context, machine learning methods may facilitate this process, allowing a fast and efficient screening of compounds in libraries and databases with reduced cost and revolutionizing the process. , The last decades have introduced artificial intelligence techniques, such as natural language processing and machine learning algorithms, to facilitate studies on drug discovery. , Considering the prospection of natural products-based compounds to the development of new anti- T. cruzi drugs, several studies reported the use of machine learning approaches integrated with phenotypical assays or validated drug targets, such as cruzain. Based on these aspects, this work focused on constructing a natural product data set with in vitro anti- T. cruzi activity. The obtained data set was used to build and validate two machine learning models capable of predicting whether a natural product will be active against intracellular forms of T. cruzi.…”
Section: Introductionmentioning
confidence: 99%